РАҲБАР ҚОБИЛИЯТИНИНГ ПСИХОЛОГИК ТАФСИФИ - Сапаров, Ш.Б. (SCIENCE and SOCIETY, 2024)
This article deals with psychological characteristics, abilities in management process acquired for senior personnel and consider practical recommendations for their development and improvement.
Keywords: psychology of management; abilities; personality of the leader; conflict management; self-development; successful specialist; skill development; practice